Uji Widal (Widal Test) - Akhmad Sudibya (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2012)
Widal Test is one of the application of diagnostic immunology in the diagnosis of typhoid fever. Widal Test must be taught at the school of medicine although some physicians opines that this test is quite obsolete. In real life there are stillmany physicians in developing countries who consider this test as very instrumental in the diagnosis of typhoid fever.